2011
DOI: 10.1590/s0102-86502011000100010
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of methylene blue and vitamin E in prevention of abdominal postoperative adhesion formation in rat uterine horn models: Biochemical and histopathologic evaluation

Abstract: Comparação do azul de metileno e vitamina E na prevenção de aderência abdominal pós-operatória em corno uterino de ratos. Avalição bioquímica e histopatológica ABSTRACT Purpose:To compare the effects of vitamin E and 1% methylen blue solutions on prevention of experimentally induced adhesions in rats. Methods: Thirty seven female Spraque Dawley rats were randomized into four groups. First group was kept as sham operated group. An adhesion model was constituted on the left uterine horn of the other groups. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…[57][58][59][60] Conversely, catalase or other antioxidants can also be administered therapeutically, in various pre-clincal models, which then prevents the onset of fibrosis. [61][62][63][64][65][66] In this context, it is interesting to note that activated myofibroblasts are known to produce and secrete hydrogen peroxide, which can have deleterious paracrine effects on adjacent normal epithelial cells. 67 Furthermore, breast cancer patients show systemic evidence of increased oxidative stress and a decreased anti-oxidant defense, which increases with aging and tumor progression.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…[57][58][59][60] Conversely, catalase or other antioxidants can also be administered therapeutically, in various pre-clincal models, which then prevents the onset of fibrosis. [61][62][63][64][65][66] In this context, it is interesting to note that activated myofibroblasts are known to produce and secrete hydrogen peroxide, which can have deleterious paracrine effects on adjacent normal epithelial cells. 67 Furthermore, breast cancer patients show systemic evidence of increased oxidative stress and a decreased anti-oxidant defense, which increases with aging and tumor progression.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Thus, the reduced rate of colonic adhesions was probably reached due to the antioxidant mechanism of MB solution over the colonic serosa and consequent enhanced fi brinolysis. Such hypothesis was confi rmed in other trials involving the uterine horn deserosation (KLUGER et al, 2000;YILDIZ et al, 2011) or cauterization (CETIN et al, 2003), cecal serosa damage (RAŞA et al, 2002;MAHDY et al, 2008), section and anastomosis of the right colon (DINC et al, 2006) and parietal peritoneum ischemia (HEYDRICK et al, 2007) in blinded controlled trials rats.…”
Section: Resultsmentioning
confidence: 70%
“…Colonic adhesions were diagnosed in two (20%) out of ten bitches that received 1mg kg -1 of 1% MB solution intraperitoneally, while eight (80%) out of ten animals from CT group which presented colonic adhesions (Figure 1-D). Deserosation, desiccation and ischemia/reperfusion injuries usually lead to acute and short-term formation of ROS (BINDA et al, 2003), which can be controlled by methylene blue (RAŞA et al, 2002;HEYDRICK et al, 2007;YILDIZ et al, 2011). Thus, the reduced rate of colonic adhesions was probably reached due to the antioxidant mechanism of MB solution over the colonic serosa and consequent enhanced fi brinolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Intraperitoneally-administered saline solution exerts its efficacy through diluting the inflammation and clearing the inflammatory mediators from the surgical area [2]. Some authors have revealed that MB can act on the adhesiontissues by reducing the reactive oxygen radicals and inhibiting the accumulation of inflammatory cells [18]. Nonetheless, Panahi et al reported that MB had no activity on inflammation.…”
Section: Discussionmentioning
confidence: 99%